THE MODERN UKRAINIAN ARMY THROUGH A GENDER PRISM - Bobrova, Yu.; Bobrov, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The analysis of numerous scientific publications shows the great relevance of gender research at the present stage of Ukrainian social development, in almost all areas of social relations. In Ukraine, the solution of the gender issue in the spheres of security and defense of the state has long remained at a conservative level. The events in the east of the country, which led to a gender breakthrough, were a significant impetus in this area. As for ensuring equal participation of men and women in the functioning of the Ukrainian army, the implementation of such a gender balance can transform the image of the armed forces from an institution associated mainly with violence and hostilities, an institution more combined with peace and democratization. The article analyzes the introduction of a gender perspective in Ukraine in the studied issues and the dynamics of establishing a gender balance in the military organization of the state; impact on existing trends in legislative initiatives. It is stated that the modern Ukrainian army is more "male", although women are admitted to military service, they do not take part in making socially important decisions, do not hold high military positions, and career growth is difficult for them. Emphasis is placed on the still existing stereotypical perception of a serviceman as a man, to change which requires social transformations, changes in people’s consciousness and, accordingly, an objective view of the problem. It also refers to the fact that the set of measures declared by the state to ensure equal rights and opportunities for women and men is a theoretical mechanism for implementing the principle of gender equality, including in the Armed Forces of Ukraine. However, in practice, in our opinion, it is almost ineffective. It is stated that providing equal opportunities for men and women in access to military service, building their own careers, improving their professional level should be realized through the creation of favorable conditions for combining work and all other aspects of life to achieve gender democracy. The main problems of gender equality in the Armed Forces of Ukraine are identified, which are largely based on social stereotypes of pre-defined roles for men and women.